Desain dan Evaluasi Struktur Sasis Kendaraan Listrik Roda Tiga Menggunakan Metode Elemen Hingga: Penelitian - Permadi, Yayang; Siswantoro, Dwi Heru (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The chassis is the main structure that supports the entire load of a vehicle, making static strength evaluation essential in the development of three-wheeled electric vehicles. This study aims to design and analyze a chassis structure made of aluminum alloy 6061-T6 using the Finite Element Method (FEM) in ANSYS Workbench software. The simulation was carried out under vertical loads ranging from 0 – 600 kg, equivalent to forces of 0 – 5884 N. The analyzed parameters included equivalent stress (Von-Mises), total deformation, and safety factor (FoS). The simulation results show that maximum stress increased from 20.96 MPa under no load to 285.71 MPa under an overloading condition of 600 kg. Maximum deformation reached 7.25 mm, while the FoS decreased from 3.95 at no load to 0.29 at 600 kg. The FoS values of less than 1, even under the normal load of 200 kg, indicate that the initial chassis design does not meet safety criteria. This study highlights the necessity of design modification, particularly in the front cross members, to ensure that the chassis structure can safely withstand operational loads.